INFLUENCE ENVIRONMENT WORK AND TECHNOLOGY INFORMATION TO LECTURER COMPETENCY AND PERFORMANCE - Ariyanto Masnun; Panji Ulum; Tarjo -; Nanik Istianingsih; Zulkifli - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Literature Review Articles on the Influence of the Work Environment, and Information Technology towards Competency dn Performance Lecturer is a scientific article that aims to build research hypotheses on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method for writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media . The results of this Literature Review article are: 1) The work environment influences competence; 2) Information Technology influences Competency; 3) The work environment influences lecturer performance; 4) Information Technology influences Lecturer Performance; and 5) Competency influences Lecturer Performance. Apart from these 2 exogenous variables which influence the endogenous variables Lecturer Competence and Performance there are many other factors including variables x3, x4 and x5